MASTER-D W-MOOC PLATFORM BASED MEDIA AS AN ONLINE LEARNING SOLUTION FOR DYSLEXIC ACCOUNTING STUDENTS - Aldi Adi Pratama; Hans Pangaribuan; I Gede Yoga Widnyana; Sifa Hardiyati Fatikha; Ratih Pratiwi; Warista Yessy Sakinah (JRAK, 2022)
Health protocol rules during the New Normal period due to the COVID-19 virus pandemic in Indonesia are serious obstacle, especially the online learning process in universities. Accounting students are required to excel in attending lectures and online practice, including accounting students with dyslexia. This study uses a qualitative descriptive method with naturalistic and interpretive paradigms that describe solutions for dyslexic students in adjusting to being able to complete their education and can be realized at the time of graduation. Subjects consisted of senior professional educators from Dyslexia Center Indonesia (DCI). The Open Online Course (W-MOOC) is needed for people with dyslexia as a learning solution to improve the innovation ability of applied accounting skills, and prepare graduates' competencies according to their field of study.